Total Quality Management & Service Sector - Alsolamy, Afnan Atiah; Albeladi, Khulood Salem; Hasan, Syed Hamid (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The following paper highlights the domination of quality service and adaptation of Total Quality Management in the service Industry. It tries to explain that along with the increasing awareness in the society in respect to culture, education and the living standard, there is an increasing demand for quality service. It is one of the factors that is forcing the service industry to adopt TQM (total quality management) as the measures to improving quality of service. It has been observed that TQM is being accepted increasingly in the last decade by the service sector which clearly signifies that service quality is treated as a crucial factor for survival, Success & growth by the companies. This has led to an increased interest in service quality recently, and TQM concepts increasingly being applied in literature for service sector